Ctenopharyngodon idellus DDX41 initiates IFN I and ISG15 expression in response to GCRV infection. Issue 106 (November 2020) - Hu, Jihuan; Xu, Xiaowen; Wang, Shanghong; Ge, Gang
Abstract: As a member of DExD/H-box helicase family, DDX41 (DEAD box polypeptide 41) acts as an intracellular DNA sensor that induces type I IFN expression in mammals. Fish DDX41 shares some similar properties with the mammalian counterparts. In this study, a DDX41 orthologous gene from grass carp ( Ctenopharyngodon idellus ) ( CiDDX41 ) was cloned and characterized. The ORF of CiDDX41 encodes a polypeptide of 614 amino acids. Multiple alignments showed that DDX41 is highly conserved among different species. Phylogenetic tree analysis revealed that CiDDX41 shares a high degree of homology with Sinocyclocheilus rhinocerous DDX41 . CiDDX41 is highly expressed in kidney, intestines, liver and spleen. Their expressions are up-regulated more obviously after the treatment with GCRV. Over-expression of CiDDX41 in CIK cells increases the transcription level of grass carp IFN I and ISG15 . On the contrary, knockdown of CiDDX41 inhibits the IFN I and ISG15 transcription. Moreover, a part of CiDDX41 translocates from the nuclear to cytoplasm to interact with grass carp STING (CiSTING). In CIK cells, overexpression of CiDDX41 and CiSTING can promote the phosphorylation and nuclear-cytoplasm translocation of grass carp IRF7 (CiIRF7) and then acutely up-regulate the IFN I and ISG15 expression. However, the knockdown of CiDDX41 inhibits the phosphorylation IRF7. Taken together, all these results above suggested that CiDDX41 performs as an activator for innate immune through STING-IRF7 mediated signaling pathway. Highlights: A DDX41 orthologous gene from grass carp (Ctenopharyngodon idella) is cloned and identified. GCRV induces the nuclear-cytoplasm translocation of C. idella DDX41. C. idella DDX41 interacts with C. idella STING and then initiates IFN I and ISG15 expression in response to GCRV infection. C. idella DDX41 and C. idella STING promote the phosphorylation and nuclear translocation of IRF7.